Amongst Mathematicians Teaching and Learning Mathematics at University Level - Nardi, Elena (Mathematics Teacher Education, 2008)
Amongst Mathematicians offers a unique perspective on the ways in which mathematicians perceive their students' learning, teach and reflect on their teaching practice; also on how they perceive the often fragile relationship between the communities of mathematics and mathematics education. Elena Nardi employs two fictional, yet entirely data-grounded, characters to create a conversation on these important issues. While personas are created, the facts incorporated into their stories are based on large bodies of data including intense focused group interviews with mathematicians and extensive analyses of students' written work. This book demonstrates the pedagogical potential that lies in collaborative undergraduate mathematics education research that engages mathematicians, researchers and students. Nardi also addresses the need for action in undergraduate mathematics education and offers a discourse for reform through demonstrating the feasibility and potential of collaboration between mathematicians and mathematics education researchers. Amongst Mathematicians is of interest to both the mathematics and mathematics education communities including university teachers, teacher educators, undergraduate and graduate students, and researchers.